Simulation of Methane Emission from Rice Paddy Fields in Vu Gia-Thu Bồn River Basin of Vietnam Using the DNDC Model: Field Validation and Sensitivity Analysis - Minh, Ngô Đức; Trịnh, Mai Văn; Wassmann, Reiner; Sander, Bjorn Ole; Hòa, Trần Đăng; Trang, Nguyễn Lê; Khải, Nguyễn Mạnh (VNU Journal of Science: Earth and Environmental Sciences, 2015)
Irrigated rice cultivation plays an important role in affecting atmospheric greenhouse gas concentrations. In recent years, extrapolation and simulation of impact of farming management on GHGs fluxes from field studies to a regional scale by models approach has been implementing. In this study, the DeNitrification & DeComposition (DNDC) model was validated to enhance its capacity of predicting methane (CH 4 ) emissions from typical irrigated rice-based system in Vu Gia-Thu Bồn River Basin with two water management practices: Continuous Flooding and Alternate Wetting-Drying.2 rice field experiments were conducted at delta lowland (Duy Xuyen district) and midland (Dai Loc district), considered as  typical regions along topography transect of study areas. The observed flux data in conjunction with the local climate, soil and management information were utilized to test a process based DNDC model, for its applicability for the rice-based system. The model was further refined to simulate emissions of CH 4 under the conditions found in rice paddies of study area. The validated model was tested for its sensitivities to variations in natural conditions including weather and soil properties and management alternatives. The validation and sensitive test results indicated that (1) the modeled results of CH 4 emissions showed a fair agreement with observations although minor discrepancies existed across the sites and treatments; (2) temperature factor changes had considerable impact on CH 4 emissions; (3) soil properties affected significantly on CH 4 emissions; (4) varying management practices could substantially affect CH 4 flux from rice paddies. It was suggested that DNDC model is capable of capturing the seasonal patterns as well as the magnitudes of CH 4 emissions from the experimental site in Vu Gia-Thu Bồn River Basin. Keywords :  DNDC model, validation, Methane (CH 4 ), rice paddy, Vietnam.